Financial sector: Upward trend in share of women on corporate boards progressing only in small steps - Elke Holst; Anja Kirsch (DIW Economic Bulletin, 2014)
Last year, more women were appointed to the executive boards of major financial institutions. The share of women on the executive boards of banks and savings banks at the end of 2013 was a good six percent, which represents an increase of almost two percentage points over the previous year. This increase is primarily attributable to changes at private financial institutions and cooperative banks. At the public banks, however, both the share of women on executive boards and changes over the previous year were below average. The share of women on supervisory boards in this area of the financial sector actually decreased. Since the private and cooperative banks were not able to compensate for this, the trend toward more women on the supervisory boards of the 100 largest financial institutions was broken. At the end of 2013, the share of women on supervisory boards was just over 17 percent, but this figure was just under 18 percent one year previously. The percentage of women on the executive boards of insurance companies was slightly higher than at the banks (nearly nine percent; up almost three percentage points) but slightly lower on supervisory boards (over 16 percent; up one percentage point). Since the initial values were so small, this was not enough to overturn the overwhelming predominance of men in the highest decision-making bodies of companies in the financial sector-despite more than half of employees being women. Considerable efforts and structural changes are needed if even remotely egalitarian structures on corporate boards are to be achieved in the foreseeable future. The challenges faced by public financial institutions are at least as difficult as they are for other institutions. Proactive human resource development policies would be a good start, but they require clear targets and timelines.
Keywords: G2; J16; J78; L32; M14; M51; 330; financial sector; board diversity; women CEOs; gender equality; management; public and private banks; insurance companies; central banks